THE INFLUENCE OF LIQUIDITY, PROFITABILITY, AND SOLVENCY TOWARD FINANCIAL DISTRESS OF CONSUMER GOODS INDUSTRY LISTED IN INDONESIA STOCK EXCHANGE - Edoardo Edoardo; Friyan Friyan (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
Every company main goal is to generate more profit to its shareholders. However, in the journey of that, many companies fall into bankruptcy because of indecision, mismanagement, and lack of knowledge. Before bankruptcy, the company financial conditions will show some traces of falling into bankruptcy, which is a state called as financial distress. Because of lack of knowledge, indecision, and wrong judgment, they end up liquidate their assets or even worse, falling into bankruptcy. Thus, financial distress information is necessary for managements to know about, not only companies, but also investors can benefits from this information as they now know which company is currently in financial distress and might not bring profit to them. Therefore, in this research study, writer will research several factors that influence financial distress and how will they influence it. Thus, in this research study, the dependent variable is financial distress that is calculated using Altman Z-Score. Meanwhile, the independent variables are Liquidity (Current Ratio), Profitability (Return on Asset ratio), and Solvency (Debt to Asset Ratio). The data collection method that is used in this research is the secondary data where the data that is gathered in this research is collected by using the documentation method. The data that is gathered will be in form of the financial statement that is published by the company on the Indonesia Stock Exchange. The data analysis in this research will be using numerical as well as the statistical calculation test which will have the purpose to test the hypothesis of the research. In order to help with the statistical calculation in the research, a window program called SPSS (Statistical Package for Social Science) will be used. There are some tests that will be used in this research which are descriptive test, classic assumption test, as well as Hypothesis testing.